Second Near‐Infrared Absorbing Agents for Photoacoustic Imaging and Photothermal Therapy. Issue 11 (17th September 2019) - Lyu, Yan; Li, Jingchao; Pu, Kanyi
Abstract: Photoacoustic (PA) imaging and photothermal therapy (PTT) provide useful tools for diagnosis and treatments of diseases. However, current applications of PA imaging and PTT are greatly limited by their relying on light source in the first near‐infrared (NIR) window (NIR‐I, 750–1000 nm), which shows shallow tissue penetration depth. Recently, this predicament is addressed by the use of second NIR (NIR‐II) light ranging from 1000 to 1700 nm due to reduced light–tissue interaction and increased allowable power density for light irradiation. Since a few endogenous biomolecules can absorb or emit NIR‐II light, it is necessary to develop contrast and therapeutic agents used for PA imaging and PTT in the NIR‐II window. This review summarizes the recent progresses of NIR‐II absorbing optical agents for PA imaging and PTT in living animal models. The prominent performance of NIR‐II PA imaging and NIR‐II PTT is first introduced with the use of optical agents, followed by discussion of the applications of NIR‐II PTT under the guidance of NIR‐I or NIR‐II PA imaging. At last, challenges and perspectives of NIR‐II absorbing optical agents for PA imaging and PTT are proposed. Abstract : The recent progress of second near‐infrared (NIR‐II) absorbing agents for photoacoustic (PA) imaging and photothermal therapy (PTT) is summarized here. Due to the deeper tissue penetration and higher maximum permissible exposure of NIR‐II light over NIR‐I light, NIR‐II PA imaging and NIR‐II PTT show improved diagnostic and therapeutic efficacy.